Unraveling the Role of Arg4 and Arg6 in the Auto‐Inhibition Mechanism of GSK3β From Molecular Dynamics Simulation. (13th May 2014) - Mou, Linkai; Li, Molin; Lu, Shao‐Yong; Li, Shuai; Shen, Qiancheng; Zhang, Jian; Li, Chuangang; Lu, Xuefeng
<x xml:space="preserve">Abstract</x> Glycogen synthase kinase 3β (GSK3β) is a multifunctional serine/threonine protein kinase that is involved in several biological processes including insulin and Wnt signaling pathways. GSK3β can be phosphorylated by the protein kinase B (PKB). The mutations of Arg4 and Arg6 to alanine at N‐terminal GSK3β have been reported to impair its ability to autophosphorylate at Ser9. Despite the extensive experimental observations, the detailed mechanism for the auto‐inhibition of GSK3β has not been rationalized at the molecular level. In this study, we have demonstrated the structural consequences of GSK3β R4A and R6A mutations and the atomic changes that influenced the loss of PKB‐binding affinity. Molecular dynamics simulation results suggested significant loss in atomic contacts in the R4A and R6A mutant systems compared to the wild‐type system. Furthermore, we observed many notable changes (such as conformation, residues motions, hydrogen bonds, and binding free energy) in the mutated GSK3β–PKB complexes. Loss of binding affinity in the mutated systems rendered the decrease in GSK3β phosphorylation, which, in turn, impaired the auto‐inhibition of GSK3β. The significant outcomes obtained from this study can explain the auto‐inhibition of GSK3β and maybe facilitate type 2 diabetes mellitus researches and in developing the potent drug therapies.